The Relationship between Participation Funds and Macroeconomic Variables: SVAR Analysis Approach - Yavuz Demirdögen; Fatih Kaplan (Türkiye İslam İktisadı Dergisi)
Participation banks are in the same financial environment with the conventional banks, so the mac- ro-economic variables are expected to affect the participation funds. The purpose of this study is to examine the relationship between participation funds and macroeconomic variables for Turkey. The relation between the total Turkish currency funds in participation banks and macroeconomic variables is examined using the weekly data se- ries from 10th of July 2015 to 5th of November 2018 by applying VAR and SVAR analysis. The total amount of the deposits of participation banks, weighted average interest rates, Borsa Istanbul gold prices, deposit interest rates of conventional banks, M2 defined money supply and total foreign exchange reserves of Central Bank of the Turkish Republic and USD exchange rate data were used as the secondary data tools. As a result of the VAR analysis, it was found that the total deposits of Islamic banks are primarily affected by money supply and the quarterly deposit in- terest rates of conventional banks. The SVAR analysis on the basis of these variables reveals that there is a positive correlation between money supply and participation funds while the relation is negative with the quarterly deposit interest rates of conventional banks and the participation funds. According to these analyses, participation funds benefit from the expansionary monetary policy, however; the interest rate policy of conventional banks negatively affects the fund inflow of the Islamic banks.